Ijtihad and Its Application in Financial Economics - Annisa Afwani; Dinda Nurayuni Humaira; Elva Mahmudi (PT ARFA DIGITAL TECHNOLOGY, 2025)
This study discusses the role of ijtihad in the innovation of Islamic banking and financial products, focusing on products such as Sukuk and Murabahah. Ijtihad is important in developing these products to comply with Islamic principles, especially in facing challenges from the conventional financial system based on usury. Sukuk, as an alternative to conventional bonds, is based on ownership of real assets, while Murabahah is a financing method that does not involve interest. In addition, this paper also highlights the challenges faced by Islamic fintech, especially in the P2P lending model, which requires ijtihad to ensure compliance with Islamic principles. The author emphasizes the importance of general principles in muamalah, such as the prohibition of usury and injustice, as well as the need for careful ijtihad to maintain the relevance of Islamic financial products to the needs of the times. Obstacles in the ijtihad process, including differences of opinion among scholars, the complexity of modern financial products, and limited resources, are also discussed. In addition, the role of women in contemporary ijtihad is recognized as an important contribution in providing new perspectives and fighting for gender justice.